Consumers' perceptions on the service quality in the motor vehicle repair and service industry: an exploratory study in Klang Valley, Malaysia - Abu Bakar, Elistina; Amin, Naemah (Universiti Putra Malaysia Press, 2011)
Motor vehicle repair and service are common and regular services used by consumers in Malaysia. The high demand for the these services is contributed by the continued increase in the number of registered vehicles and the number of driving licence issued annually. There are also many compliants reported in the Tribunal for Consumer Claims (TCC) in relation to this industry. Thus, this study aimed to identify the perceptions of consumers towards the quality of the services provided by motor vehicle garages. A total of 400 respondents participated in the study through simple random sampling and data were collected using a self-administered questionnaire.The result of this study indicated that most of the respondents generally had low and moderate perceptions of the service quality.